Cigarette and alcohol use among university students: an evaluation in terms of depressive symptoms and hopelessnessa - Babacan Gümüş, Aysun (Journal of Dependence, 2015)
Objective: The aim of this study was to analyze the relationships between cigarette and alcohol use among university students and depressive symptom and hopelessness. Methods: The sample of the study was composed of 374 students studying at the state university. Students were selected by stratified random sampling proportional to the total number of students in the schools of university. The data were collected by Introductory Information Form, Beck Depression Inventory (BDI) and Beck Hopelessness Scale (BHS). In the analysis of data, Kolmogorov-Smirnov test, number, percentage, median, 25th-75th. percentiles, Kruskal Wallis test, Kruskal-Wallis test, Mann Whitney U test and Spearman Rank Correlation analysis were used. Results: The mean age of the students was 21.05±2.33. 39% of the students used cigarette and 57,8% used alcohol. The median score for BDI was 10,50 and the median score for BHS was 4,00. Depressive symptoms level was high in 25,9% of the students. A statistically significant difference was found in BDI median values of students according to smoking status (z=-2.378, p<0.05). A statistically significant difference was found in BHS median values of students according to alcohol use (z=-2,143, p<0,05). Statistically significant differences were not found in BDI and BHS median values of students according to the amount of smoking and alcohol use (p>0,05). Conclusion: The results show that use of cigarette and alcohol was high level among university students who participated in the study. It was found out that depressive symptoms level was high in students using cigarette and hopelessness level was high in students using alcohol. Thus, actions to prevent university students from use of cigarette and alcohol and actions to protect their mental health should be increased. To reduce smoking and alcohol use among students may be helpful for early diagnosis and treatment of depressive symptoms with preventive mental health practices.